Humanising strategic planning through Ulū Al-Albāb approach in post normal times for sustainable performance - Mhd. Sarif, Suhaimi; Zainudin, Dolhadi; Yahya, Rohaziah (Meso Publishing, 2020)
This study postulates that strategic planning process is humanisable through ulū al-albāb approach for sustainable performance and development in all sectors of life. In business sector, strategic planning is very important and it deploys talents and potentials for profitability maximisation in the trade-off of sustainability development. There are huge of inhumanisation, unethical practices, and irresponsible production in the agenda of maximising profit. The cost minimisation has been transferred by force to the society in terms of social illness, trust deficit, and environmental problems. This study explores strategic planning activities of selected companies in Malaysia. The study found that the level of humanisation from ulū al-albāb is limited to the bureaucracy and business models.